Prevalence of malaria and associated factors among febrile children under 15 years at Bududa General Hospital, Eastern Uganda - Benson Okongo; Daisy Asiimwe; Clinton Olong; Enoch Muwanguzi; Robert Wagubi (Malaria Journal)
Abstract Background A significant portion of malaria-related deaths occur in Africa, and Uganda is an endemic region where malaria remains a public health concern. This study aimed to determine the prevalence of malaria and its associated factors among febrile children under 15 years of age at Bududa General Hospital, Eastern Uganda. Methods This cross-sectional study was conducted between April and June 2023. Informed consent was obtained from parents/guardians before 250 febrile children below 15 years were enrolled in this study. A structured questionnaire was administered to parents/guardians to collect sociodemographic characteristics and identify factors associated with malaria. Venous blood samples were collected from the children and screened for the presence of malaria parasitaemia using blood smear microscopy. The data collected were entered into an Excel spreadsheet and analysed using STATA version 14. Logistic regression models were used to determine the factors associated with malaria, and we considered ≤ 0.05 as the level of significance. Results Out of the 250 study participants, the overall prevalence of malaria was 111(44.4%). Among the children who tested positive for malaria, 98 (88.3%) had Plasmodium falciparum, 11 (9.9%) had Plasmodium malariae, and (1.8%) had Plasmodium ovale infection. The mean parasite count was 21,951 parasites/µL of blood. The highest parasite count was 154,387 parasites/µL of blood, and the lowest count was 146 parasites/µL of blood. The prevalence rates of low, moderate, and high malaria parasitaemia were 46.8%, 28.0%, and 25.2%, respectively. In the multivariate analysis, the factors associated with malaria infections were older age; 1 to 5 years (p = 0.013), 6 to 10 years (p = 0.000), 11 to 15 years (p = 0.000), secondary education (p = 0.050), and no use of insecticide-treated bed nets (p = 0.002). Conclusion The prevalence of malaria among febrile children in this study was high, with nearly half of the participants showing severe infections. Health education on the correct use of insecticide-treated mosquito nets should be prioritized to help control malaria.